The influence of high-intensity functional training versus resistance training on the main physical fitness indicators in women aged 25-35 years - Chukhlantseva, Natalia; Cherednychenko, Inna; Kemkina, Viktoria (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Improving the physical fitness and performance of young women depends on the differentiated selection of methods and the amount of the load, the optimal selection of training methods. The aim of the study was to evaluate the influence of 24-week high-intensity functional training (HIFT) program compared to the resistance training (RT) program on healthrelated physical fitness indicators of women aged 25-35. Material and Methods. Thirty-six women (age 30.23 ± 3.5 years) were divided into two groups: experimental (EG; n = 18) – HIFT program, and control group, practicing RT (CG; n = 18). Both programs included exercises with massage rollers, exercises to overcome the weight of their own body, with fitness accessories, three times a week for 24 weeks. Classes in the EG were distinguished by performing 2-3 sets of exercises 15-20 times each (at 85-95% HRmax), separated by 10-30 s to 1 min periods. CG participants trained with an intensity of 60-70% HRmax. Differences in the effectiveness of HIFT and RT were determined by changes from the baseline to the final level in health-related indicators and physical fitness, evaluated by the ALFA-fitness program. Results. All scores in the EG and CG, except for the “one-leg stand” (p = 0.056) in CG, improved (p < 0.01 pre- vs post-training increases for each group). Post-training, waist circumference (69.28 ± 5.00 vs 74.19 ± 6.30 cm, p = 0.014), BMI (22.09 ± 1.54 vs 23.27 ± 1.51 kg/m2, p = 0.027), “figure-of-eight run” (7.96 ± 0.61 vs 9.03 ± 1.24 s, p = 0.002), “jump-and-reach” (32.33 ± 4.79 vs 26.00 ± 5.25 cm, p = 0.001), “2-km walk test” (15.38 ± 0.93 vs 16.86 ± 1.16 m, s, p = 0.0001) were better in EG than in CG, respectively. Conclusions. RT and HIFT are effective in terms of health and fitness. Compared to RT, HIFT training is more effective in reducing waist circumference, BMI, increasing agility and lower muscle strength, and improving cardiorespiratory fitness
Keywords: multifunctional exercises; circular training; working capacity; balance; muscle strength